How Did Local Governments Recover Their Financial Condition? Lessons from Citizen Participation - Ji Hyung Park (Transylvanian Review of Administrative Sciences, 2023)
This study offers lessons for overcoming future economic crises by examining whether democratic management helped local governments recover their financial condition. During the Great Recession, local governments were forced to make painful decisions regarding increased taxes and user charges, and cuts in public services. Several case studies provide evidence that citizen participation allows localities to increase property taxes as well as cut public services. However, broader, systematic empirical research is lacking. This study found that local governments with participatory budgeting were more likely to improve their financial condition during the Great Recession. The results allow us to identify the role of citizens in fiscal decision-making, offering lessons on how local governments can overcome possible fiscal crises in the future.